Performance Investigation of Asphaltene Adsorption at a Carbonate Rock Surface Spectroscopy Experiment and Molecular Simulation - Ma, Litao (Langmuir : the ACS journal of surfaces and colloids, 2024)
Investigation of asphaltene adsorption at rock surfaces plays an important role in enhanced oil recovery (EOR) for the petroleum industry. In this work, the interaction performances of asphaltene adsorption at carbonate dolomite and calcite surfaces are investigated based on experimental and simulation insights. On the one hand, macroscopic interaction performances were investigated by spectroscopy experiments to obtain the Langmuir thermodynamic model and pseudo-second-order (PSO) kinetic model. The results indicated monolayer molecular asphaltene adsorption for both dolomite and calcite, while they showed 'slow adsorption-slow desorption' for dolomite but 'fast adsorption-fast desorption' for calcite. Meanwhile, dolomite showed a higher adsorption capacity with qm(dol 1) = 5.35 mg/g > qm(cal 1) = 1.28 mg/g and a stronger adsorption spontaneity with ΔGm(dol 1)θ = -7.76 kJ/mol < ΔGm(cal 1)θ = -4.76 kJ/mol. On the other hand, microscopic interaction performances were investigated for three asphaltene molecules by molecular dynamics simulation (MDS) with ∼8 Å distance-placing and 500 ps time-running. According to the results, dolomite showed higher system stability than calcite with a lower final energy of ΔEdol-cal = -58 kJ/mol, and archipelago asphaltene showed higher adsorption stability with the smallest equilibrium energy of Earch(dol) = -147 kJ/mol for albite and Earch(cal) = -89 kJ/mol for calcite. The model of molecular orientation and force dominance was proposed as the interaction mechanism for asphaltene adsorption, which "lie sideways" at low concentrations but "stands upright" at high concentrations. This work allows the performance investigation and mechanism illustration of asphaltene adsorption at rock surfaces, which can help gain a fundamental understanding of the EOR during reservoir exploitation